Review on Liposome as Novel Approach for Cancer Therapy - Singh, Lodhi Devendra; Ganju, Kuldeep; Rajpoot, Ramkumar (Asian Journal of Pharmaceutical Research and Development, 2020)
The main objective is to study the importance of liposome in drug targeting in cancer cells andgo through various research work going through on liposome. The importance of liposomes to study the flexibility to couple with the specific ligands toachieve active targeting. Cancer can be treated by surgery, radiation, chemotherapy, gene therapy, immunotherapy, hormone therapy. Cancer is the uncontrolled growth of abnormal cell anywhere in a body. The abnormal cells aretermed cancer cells, malignant cells, or tumor cells. There were 14.1 million new cancer cases, 8.2 million cancer deaths and 32.6 million people living with cancer (within 5 years of diagnosis) in 2018 worldwide. 57% (8 million) of new cancer cases, 65% (5.3 million) of the cancer deaths and 48% (15.6 million) of the 5-year prevalent cancer cases occurred in the less developed regions.